Role of public R&D funding in fuel cell: analysis on Iranian universities. (2018) - Soltanzadeh, Javad; Salami, Reza
Achieving sustainable development, environmental protection and security of energy supply are two main challenges of government in developed or developing countries. In developed countries, technological regimes and its actors have self-willingness to track advanced technologies and new knowledge (such as Fuel Cell) due to system and market failures, developing countries need to insert R&D expenditure in particular for public universities. But can governments promote FC technology only by increasing R&D funding? This paper surveyed 900 papers published by Iranian researchers from 2000 to 2014. Result is shown that: 1) Iran is 21st countries of published papers in fuel cell field; 2) most of these papers focus on PEM and SOFC; 3) more than 80% of total papers have been published by 23 public universities; 4) policymakers must create R&D network to improve funding efficiency and design effective policy to commercialize new created knowledge that encourages the demand side.